Being a patient in the intensive care unit: a narrative approach to understanding patients’ experiences of being awake and on mechanical ventilation - Marte-Marie Wallander Karlsen; Lena Günterberg Heyn; Kristin Heggdal (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Intensive care patients often struggle to communicate due to the technical equipment used for mechanical ventilation and their critical illness. The aim of the study was to achieve a deeper understanding of how mechanically ventilated intensive care patients construct meaning in the unpredictable trajectory of critical illness. Methods The study was a part of a larger study in which ten patients were video recorded while being in the intensive care. Five patients engaged in interviews about their experiences from the intensive care stay after being discharged and were offered the possibility to see themselves in the video recordings. A narrative, thematic analysis was applied to categorize the patients’ experiences from the intensive care. Results A pattern of shared experiences among intensive care patients were identified. Three main themes capture the patient’s experiences: 1) perceiving the intensive care stay as a life-changing turning point, 2) being dependent on and cared for by others, and 3) living with negative and positive ICU experiences. Conclusion The patients’ narratives revealed how being critically ill affected them, and how they understood their experiences in relation to themselves and their surroundings. The results can be used to pose important questions about our current clinical practice.